Integrating monetary and non-monetary valuation for ecosystem services in Piatra Craiului national park, Southern Carpathians: a comprehensive approach to sustainability and conservation - Chivulescu, Serban; Hapa, Mihai; Pitar, Diana; Lorenţ, Adrian; Marmureanu, Luminita; Leca, Stefan; Radu, Raul; Cazacu, Roxana; Dobre, Alexandru Claudiu; Pascu, Ionut Silviu; Marcu, Cristiana; Verghelet, Mircea; et al. (Frontiers in Forests and Global Change, 2024)
The concept of ecosystem services has gained significant attention in recent years due to the profound interdependence and interconnectedness between humans and ecosystems. In the study area, although several studies on valuation of forest ecosystem services were performed in the last years, the environmental conditions evolve and human pressures on forests intensify, thus further research is necessary to comprehensively understand the changing dynamics of these services and devise effective conservation measures. The aim was to valuate monetary and non-monetary ecosystems services in Piatra Craiului National Park using quantitative (e.g. forest management plans) and qualitative data (e.g. photo analyses of general public visitors), and to define relationships among indicators of ecosystem characteristics and servicesThe aim of this research is to valuate ecosystems services in Piatra Craiului National Park, using both monetary and non-monetary valuation methods, harmonize quantitative data (from forest management plans) and qualitative data